2019
DOI: 10.3389/fimmu.2019.02925
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Directly Enhances Osteocyte RANKL Expression and Promotes Osteoclast Formation

Abstract: Osteoimmunology peeks into the interaction of bone and the immune system, which has largely proved to be a multiplex reaction. Osteocytes have been shown to regulate bone resorption through the expression of RANKL in physiologic and pathologic conditions. TNF-α, a product of the immune system, is an important cytokine regulating bone resorption in inflammatory conditions either directly or by increasing RANKL and M-CSF expressions by osteoblasts and stromal cells. The effect of TNF-α on a wide range of cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 41 publications
2
107
0
3
Order By: Relevance
“…Activated AKT also acts as an anti-apoptotic signal, and TNF-α stimulates the AKT pathway in a cell-type-specific manner [104]. We found a trend of activated AKT phosphorylation to levels that did not reach statistical significance [16]. The results of the study supported the role of osteocytes in their potential contribution to bone destruction by increasing RANKL expression via the direct action of TNF-α.…”
Section: Tnf-αmentioning
confidence: 51%
See 3 more Smart Citations
“…Activated AKT also acts as an anti-apoptotic signal, and TNF-α stimulates the AKT pathway in a cell-type-specific manner [104]. We found a trend of activated AKT phosphorylation to levels that did not reach statistical significance [16]. The results of the study supported the role of osteocytes in their potential contribution to bone destruction by increasing RANKL expression via the direct action of TNF-α.…”
Section: Tnf-αmentioning
confidence: 51%
“…Inhibition of ERK1/2, p38, and JNK MAPKs via their respective inhibitors (U0126, SB203580, and SP600125) in osteocytes cultured with TNF-α suppressed RANKL mRNA expression to baseline levels compared with untreated cells. We also found that TNF-α activates the NF-κB pathway in osteocytes measured by p65 subunit nuclear translocation [16]. Activated AKT also acts as an anti-apoptotic signal, and TNF-α stimulates the AKT pathway in a cell-type-specific manner [104].…”
Section: Tnf-αmentioning
confidence: 57%
See 2 more Smart Citations
“…Early in vitro studies demonstrated that TNF-α could induce both cartilage degradation [62] and bone resorption [63]. Recently, TNF-α was also shown to enhance RANK-L secretion by osteocytes which further promotes osteoclastogenesis [64]. Interestingly, some studies pointed out that TNF-α can also directly induce the differentiation of monocyte/macrophage lineage cells into osteoclasts by a RANK-L-independent mechanism [65][66][67].…”
Section: Contribution Of Cytokines To Inflammation In Ramentioning
confidence: 99%